82‐1: Distinguished Paper: Glass Substrate for Micro Display Devices. Issue 1 (May 2017) - Hayashi, Kazutaka; Nomura, Shuhei; Sakai, Yusuke
Abstract : Glass substrate suitable for wearable micro display devices for augmented/virtual reality was developed. This glass has highly matched thermal expansion coefficient with that of silicon and it enables to suppress amount of warpage caused by the boding between Si and glass wafers. The glass also shows lower thermal shrinkage than that of conventional non alkali glass for thin film transistor substrate. In this paper, the effect of the temperature dependence of CTE on warpage generation after bonding process was investigated using both numerical simulation and experiment. The newly developed glass showed remarkably low warpage after the bonding process.